"The Very Seeds of Fire”: Chris Lee’s The Map Maker’s Sorrow - Morse, Donald E. (Hungarian Journal of English and American Studies, 2020)
Chris Lee’s The Map Maker’s Sorrow (1999), produced at the Abbey Theatre only six years after Ireland decriminalized suicide, proved prescient in focusing on this national health problem among the young. The very structure of the play mirrors the fragmentation and messy aftermath that suicide almost inevitably produces. The abrupt beginning, where a character that the audience does not know and cannot know kills himself, leaves the audience in a position similar to that of survivors who find a suicide. Drawing on the work of Ludwig Binswanger, Kay Renfield Jamison, and national studies of suicide the essay argues that young Jason’s suicide represents a direct challenge to life understood as an orderly progression from birth to death and as an attempt to deny the very premise of lived life itself. (DEM)